Aging in the Philippines. (8th January 2018) - Badana, Adrian N S; Andel, Ross
Abstract: The Philippines is a diverse country that will experience an increase in its aging population in the near future. The aim of this article is to provide an overview of the main issues surrounding population aging, as well as family caregiving and policies that are of concern to older adults in the Philippines. Policymakers and government leaders must plan for the expected growth in the numbers of older adults, which is likely to increase the demand for services and support for elders and their caregiving families. The Philippines' unique history and rich culture shapes its citizens' views on aging and bolsters expectations of informal caregiving for older family members. Research on aging in the Philippines and current policies must be enhanced to adequately address the needs of the country's aging citizens.